Measurement properties of self-report instruments to assess health literacy in older adults: a systematic review. Issue 11 (22nd May 2022) - Slatyer, Susan; Toye, Christine; Burton, Elissa; Jacinto, Alessandro Ferrari; Hill, Keith D.
Abstract: Background: High health literacy (HL) is important to optimise health outcomes, particularly for older people (who are substantial consumers of health services) and their adult caregivers. The aim of this systematic review was to evaluate measurement properties of HL instruments tested with these population groups. Materials and methods: Six databases (MEDLINE (OVID); CINAHL; EMBASE (OVID); PsycInfo; Scopus; Cochrane Library) were searched for studies evaluating eight measurement properties of HL tools administered to older people or their caregivers. Only studies evaluating multi-domain self-report HL tools were included in analyses, using the COSMIN methodology. Results: From 4261 unique papers located, 11 met inclusion criteria; six reported measurement properties of three HL self-report tools administered to older people (HLQ, eHEALS, and HeLMS) so are reported in this review, none involved caregiver samples. The HLQ and HeLMS were rated "moderate, " and eHEALS "low" for tool development. The HLQ, examined in four included studies, had the highest ratings and quality of evidence across the three measurement properties investigated in included papers. Conclusion: The HLQ was the most highly rated self-report HL tool of just three tested with older people. Further studies evaluating measurement properties of self-report HL tools used with older people and/or their caregivers are needed. Implications for rehabilitation: Health literacy is important to optimise health outcomes of interventions for older people and their adult caregivers. Few studies have evaluated measurement properties of self-report / multi-domain health literacy tools for this population. The Health Literacy Questionnaire (HLQ) had the highest ratings and quality of evidence across the three measurement properties investigated in included studies, and is recommended for use in rehabilitation settings.